Developing sustainable and embedded interprofessional education: threshold learning outcomes as a potential pathway : extension final report. - O'Keefe, Maree (Office for Learning and Teaching, 2015)
This is the final report from a project which built on a previous project, Harmonising higher education and professional quality assurance processes for the assessment of learning outcomes in health, which was completed in 2013. This final project activity brought a number of diverse strands together into a much-needed set of resources for the health education sector. A review of international interprofessional learning (IPL) literature was conducted. The individual component competencies from six national and international IPL/interprofessional education (IPE) curriculum/competency frameworks were mapped against Threshold learning outcomes (TLOs) for Health, and then aggregated to create a single set of IPL competency statements. A Good Practice Checklist was also developed. A panel of invited key national stakeholders from health services, government, discipline groups, professional accreditation councils and higher education institutions attended a Round Table to review and refine these documents with consensus that both could usefully guide implementation of IPL in Australia. The competency statement describes what a graduating student from any health profession can do. Each component has been deliberately described so as to be observable and measurable through standard assessment processes.